2010
DOI: 10.1270/jsbbs.60.3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of variation in sugar chain composition at the C-22 position of group A saponins in soybean, Glycine max (L.) Merrill

Abstract: Saponins are a diverse group of secondary metabolites widely distributed in plants. Some saponins in soybean seeds have medicinal properties, but the terminal acetylated sugar at the C-22 position of group A saponins in seed hypocotyls causes a bitter and astringent taste. We used cultivated and wild soybean accessions classified into four different group A saponin phenotypes, including non-acetylated A0-αg and deacetyl-Af, as parents to obtain four F 2 populations and a population of recombinant inbred lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…Inter-conversions among saponins and the complexity of their modifications seem to involve a number of glycosyltransferases and acetylases, and are implicated in the generation of bitterness and astringeny. Mutants, identified in soybean and wild soybean (Glycine soja), have defined two genetic loci, Sg-1 and Sg-2, that control these phenotypes (Takada et al, 2010). In pea, the modified saponin named DDMP (2,3-dihydro-2,5-dihydroxy-6-methyl-4H-pyran-4-one)-saponin, has been implicated in bitterness and it has been suggested that this and related compounds could interact negatively or positively with seed protein components (Heng et al, 2004).…”
Section: E the Anti-nutritional Factor Riddle In Legumesmentioning
confidence: 99%
“…Inter-conversions among saponins and the complexity of their modifications seem to involve a number of glycosyltransferases and acetylases, and are implicated in the generation of bitterness and astringeny. Mutants, identified in soybean and wild soybean (Glycine soja), have defined two genetic loci, Sg-1 and Sg-2, that control these phenotypes (Takada et al, 2010). In pea, the modified saponin named DDMP (2,3-dihydro-2,5-dihydroxy-6-methyl-4H-pyran-4-one)-saponin, has been implicated in bitterness and it has been suggested that this and related compounds could interact negatively or positively with seed protein components (Heng et al, 2004).…”
Section: E the Anti-nutritional Factor Riddle In Legumesmentioning
confidence: 99%
“…The biosynthesis of saponin A0-ag results from a recessive allele, sg-1 0 , at the same locus (Kikuchi et al, 1999;Takada et al, 2010). Here, we describe the identification of multiple alleles of the Sg-1 locus that are responsible for the structural diversity of the terminal sugar at the C-22 position of group A saponins.…”
Section: Introductionmentioning
confidence: 95%
“…Both have an acetylated sugar at the terminal position ( Figure 1A) that causes the undesirable aftertaste (Kitagawa et al, 1988;Taniyama et al, 1988b;Okubo et al, 1992). By screening more than 1000 germplasm stocks, a soybean cultivar and a wild accession were found to accumulate saponin A0-ag, which lacks the acetylated terminal sugar at the C-22 position ( Figure 1A) (Kikuchi et al, 1999;Takada et al, 2010). These findings led to breeding of cultivars useful for human food, such as Kinusayaka, which reduces the bitter taste and astringent effects (Kato et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Soybean ( Glycine max (L.) Merr.) is one of the most economically important crop plants worldwide and triterpenoid saponins are major components of secondary metabolites in its mature seeds (Tsukamoto et al ., ; Takada et al ., , ). Saponins comprise more than 2% of the dry weight of the hypocotyl in developed mature seeds (Fenwick et al ., ), and are characterized as group A saponins or 2,3‐dihydro‐2,5‐dihydroxy‐6‐methyl‐4 H ‐pyran‐4‐one (DDMP) saponins based on their chemical structures.…”
Section: Introductionmentioning
confidence: 99%
“…The diversity of sugar moieties in soybean saponins is influenced by seven alleles at three different loci: Sg‐1 , Sg‐3 , and Sg‐4 (Shiraiwa et al ., ; Tsukamoto et al ., ; Kikuchi et al ., ; Takada et al ., , ). Sg‐1 ( Glyma07g38460 ) was recently cloned and encodes a uridine diphosphate (UDP)‐sugar‐dependent glycosyltransferase (Sayama et al ., ).…”
Section: Introductionmentioning
confidence: 99%